Credit Risk Analysis and Its Impact on Financial Performance Indicators Based on Accounting Profit: An Applied Study on Saudi Stock Exchange Institutions During the period 2018 – 2022 - Salim, Alsadig Mohamed (Journal of Economic, Administrative and Legal Sciences, 2025)
The primary objective of this study is to identify the impact of credit risk on financial performance indicators based on accounting profit, measured by (return on assets and return on equity), for institutions in the Saudi Stock Exchange (Tadawul). To achieve this objective, the study adopted an analytical methodology, where data was collected from various sources, such as reports and statistical bulletins issued by the Capital Market Authority and the annual statistical reports issued by the Saudi Stock Exchange (Tadawul). This data was analyzed using appropriate statistical and analytical tools. The study used the simple linear regression method to identify the impact of credit risk on financial performance indicators based on accounting profit, measured by (return on assets and return on equity), for institutions in the Saudi Stock Exchange (Tadawul). The study reached several results, the most important of which are: the existence of a strong, statistically significant, direct correlation between credit risk and financial performance indicators based on accounting profit, measured by (return on assets and return on equity), for institutions in the Saudi Stock Exchange (Tadawul). The results of the simple linear regression also confirmed the existence of a statistically significant, positive impact of credit risk on financial performance indicators based on accounting profit, measured by (return on assets and return on equity), for institutions in the Saudi Stock Exchange (Tadawul). One of the most important recommendations of the study is the need to support and enhance the ability of financial market institutions to predict various financial risks.